PEMBELAJARAN MENULIS TEKS TANGGAPAN KRITIS PADA SISWA KELAS IX SMPN 8 PONTIANAK - Heavenlim, Natalia Rosi; Abdussamad, Abdussamad; Wartiningsih, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractIndonesian Language Learning currently used a 2013 text-based curriculum. Curriculum 2013 with the previous curriculum has a very far difference. Curriculum 2013 is applied with limited socialization. One of the new school curriculum of 2013 were junior high school 8 Pontianak. The application of the 2013 curriculum which was still new with the lack of socialization is the basis of the researchers conducting this research. This study aims to describe the learning of writing critical response texts based on the 2013 curriculum in class IX students of SMPN 8 Pontianak. The research method used was descriptive with qualitative research. Based on the results of this study concluded that 1) the learning plan (RPP), the first and the second designed by teachers in accordance with Permendikbud No. 22 of 2016 and the curriculum, 2013; 2) the implementation of critical response text learning carried out by teachers viewed from APKG 2 which contains provisions in the 2013 curriculum, has been implemented well and in accordance with what should be; 3) assessment of the learning of critical response texts carried out by the teacher was in accordance with the assessment provisions contained in the 2013 curriculum. Keywords: Critical response text, learning, 2013 curriculum,